Character Values in Relation to the Sea Story Novel by Leila S. Chudori to Learning in High School - Sansan Arini Rahmawati (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: The novel Laut Bercerita by Leila S. Chudori introduces various applied in high school learning. This study aims to identify these values and explore the implications of their application in learning Indonesian high school. This study uses a qualitative approach with content analysis techniques to identify the values of character education in the novel Laut Bercerita. The results of the study show that there are several character education values contained in this novel, including honesty, justice, friendship, simplicity, courage, and responsibility. The implications of these values for learning Indonesian in high school are improving language skills, understanding cultural values, and forming positive and constructive student character. This study also provides practical recommendations on how to integrate character education values into Indonesian language learning in senior high schools. The Novel Laut Bercerita by Leila S. Chudori has many character education values that are relevant to be applied in learning Indonesian in high school. Integrating these values into learning can help improve language skills, understand cultural values, and shape positive student character studies that wish to develop Indonesian language learning based on character education. Keywords: the value of character, storytelling marine novels, indonesian language learning in high school.